Growth participation units: A proposal for a long-term financial instrument - Tamir B. Agmon (Intereconomics, 1975)
The financing of long-term growth in developing countries has become more of a problem every year. In the following article one particular new financial instrument — Growth Participation Units — is discussed as a particular way to attract private sector long-term financing of development.
Keywords: 330; Development Financing